Effect of Insect Growth Regulators “Dimilin25% wp and Match 50 EC” Against House Fly (Musca domestica) Life Stages (Diptera: Muscidae) - Ezeddin A. Albayyar; Rafraf Abdul Aziz Abdel Qader (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was conducted to identify the effect of growth regulators “Match and Dimilin” using different concentrations on the incomplete life stages of the house fly, and calculating the percentages of egg hatching, incapability of larvae pupation and emergence of adult insects in laboratory conditions. All the concentrations showed different percentages in their effect on the life stages of the insect, whereas the effects were increased with the exposure rate increasing. However, the hatching rate for eggs in the concentration of (1000) mg/l reached to (0.00%) for the Match growth regulator, while it reached (20.50%) for the Dimilin regulator at the same concentration. In the larval stages, the percentage of larvae that reached the pupa phase in concentration of (1000) mg/l for both growth regulators was (0.00%), while the emergence rate of adults for the same concentration was reached in growth regulators Match and Dimilin for (25.33%) and (10.33%) respectively